Delayed premium payment, insurance adoption, and household investment in rural China - Liu, Yanyan; Chen, Kevin Z.; Hill, Ruth Vargas (Agricultural and Applied Economics Association, 2020)
We conduct a randomized controlled trial to examine the impacts of delayed premium payment on insurance uptake and the subsequent investment decisions among smallholder farmers in rural China. Our results show uptake among those with the delayed payment option is 10% higher than and three times as high as among those without the option. We also find a positive impact of delayed premium payment and insurance adoption on household investment in production, especially higher risk activities.